Scientific Perspectives on Adolescent Sleep Patterns, Cognitive Development, and Pediatric Health Promotion in Educational Environments Today - Nachappa, Dr. M N; Sharma, Dr. Prashant; Raj, Honey; Tripathy, Dr. Alakananda; P, Dr. Gaman; Siridhara, A L; Kumar, Dr. Selva (Adolescência e Saúde, 2026)
Though adolescence is a critical period of cognitive, emotional and social growth, this period of life has been characterized by high rates of sleep disturbances, with a number of factors contributing to this including a higher focus on academic performance and increased screen time as well as irregular lifestyle practices. Inadequate sleep quality and quantity have become a critical issue related to the learning capabilities, attention, memory, emotional control, and overall wellbeing. The present study aims at uncovering the connection between sleep patterns, cognitive growth and emotional well being of adolescents in educational settings. We used standard sleep quality questionnaires, cognitive function tests, and questionnaires of emotional health to carry out a cross-sectional survey of 200 adolescents (aged 13–18 years). It was found that 62% of the participants had poor sleep quality, and 48% slept less than 7 hours a night. Lower cognitive performance was significantly correlated with poor sleep (r = −0.54, p < 0.01) as was higher emotional distress (r = 0.49, p < 0.01). It is recommended to educate and raise awareness of parents and utilize digital-use management strategies and sleep education in schools to encourage better sleep practices and enhance adolescent health outcomes.